2013
DOI: 10.4103/0973-7847.112837
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of alkaloids: Factors, approaches, challenges and prospects

Abstract: The wide diversity of plant secondary metabolites is largely used for the production of various pharmaceutical compounds. In vitro cell tissue or organ culture has been employed as a possible alternative to produce such industrial compounds. Tissue culture techniques provide continuous, reliable, and renewable source of valuable plant pharmaceuticals and might be used for the large-scale culture of the plant cells from which these secondary metabolites can be extracted. Alkaloids are one of the most important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 41 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…The most valuable forms can then be selected and used to establish large-scale culture systems (suspension cell culture or organ culture in bioreactors, or as regenerated plants) for production of those compounds (Ahmad et al 2013;Bourgaud et al 2001;Rout et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The most valuable forms can then be selected and used to establish large-scale culture systems (suspension cell culture or organ culture in bioreactors, or as regenerated plants) for production of those compounds (Ahmad et al 2013;Bourgaud et al 2001;Rout et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They provide a pure continuous source of secondary metabolites independent of geographical or climatic conditions and within a short time period as compared to the extraction from wild plants (Gonçalves and Romano, 2018). In vitro culture systems act as an alternative method for the production of secondary metabolites, thereby conserving the natural sources (Ahmad et al, 2013). In addition to enabling the cultivation of many plants with products of high medicinal value, plant cell cultures are considered as a promising source for the sustainable production of pharmaceutically valuable secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to cultivate the plant to fulfill the increasing demand of reserpine and the promising option in the pharmaceutical world due to the presence of the significant chemical compounds in roots. [10] A study showed positive effect of Kinetin and NAA on callus induction and root formation in vitro grown with leaf explants if we use suitable concentrations of them, alone or in combination [11]; [12] NAA as growth regulator generates the growth of root, and maximum shoots grew from callus of explant inoculated in medium containing BAP [2.0 mg/L] plus NAA [0.5 mg /L] [1]. Reported that explant of R. serpentine grew in MS media supplemented with NAA [0.01 mg/L and BAP [0.5 mg/L] resulted in two buds in primary culture and four buds in subsequent sub-culture [13].…”
Section: Introductionmentioning
confidence: 99%